Taming the wild relatives of the common bean - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Many useful genes have been identified in wild forms and distant relatives of important staples but they are often not used in conventional plant breeding. At the International Centre for Tropical Agriculture (CIAT), Colombia, scientists have been...